2020
DOI: 10.3390/nu12123861
|View full text |Cite
|
Sign up to set email alerts
|

Association between Geriatric Nutritional Risk Index and Mortality in Older Trauma Patients in the Intensive Care Unit

Abstract: The geriatric nutritional risk index (GNRI) is a simple and efficient tool to assess the nutritional status of patients with malignancies or after surgery. Because trauma patients constitute a specific population that generally acquires accidental and acute injury, this study aimed to identify the association between the GNRI at admission and mortality outcomes of older trauma patients in the intensive care unit (ICU). Methods: The study population included 700 older trauma patients admitted to the ICU between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Su et al 33 found an independent association between GNRI and mortality in geriatric patients with moderate to severe traumatic brain injury. Other studies corroborated this association between malnutrition and mortality as well as found an association between GNRI, prolonged hospital LOS, and poor functional outcomes 12,14,34 . With this study, we have identified a population that can be identified early in the hospital course as high risk for poor clinical outcomes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Su et al 33 found an independent association between GNRI and mortality in geriatric patients with moderate to severe traumatic brain injury. Other studies corroborated this association between malnutrition and mortality as well as found an association between GNRI, prolonged hospital LOS, and poor functional outcomes 12,14,34 . With this study, we have identified a population that can be identified early in the hospital course as high risk for poor clinical outcomes.…”
Section: Discussionsupporting
confidence: 66%
“…Other studies corroborated this association between malnutrition and mortality as well as found an association between GNRI, prolonged hospital LOS, and poor functional outcomes. 12,14,34 With this study, we have identified a population that can be identified early in the hospital course as high risk for poor clinical outcomes. Accordingly, this population may benefit from early interventions of nutrition as a modifiable risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…This is contradictory to some US studies which demonstrated that patients with major trauma taken directly to a trauma center had lower mortality than those seen at other hospitals and subsequently referred to a trauma center for definitive care [ 4 , 11 ]. In Taiwan, most traffic accidents are motorcycle accidents that occur in relatively crowded streets, and the transport times of patients to the emergency room are short (average 12 min for Taipei according to government data [ 12 ] and 18 min for Kaohsiung according to our previous analysis) [ 13 , 14 ]. Therefore, we believe that the short transportation time from the accident scene to the emergency room may partly explain why there was no significant difference in the mortality rate between the patients who were transferred from other hospitals and those transported directly to trauma centers first.…”
Section: Discussionmentioning
confidence: 99%
“…9 Malnutrition risk defined by MUST was associated with higher mortality at 1-year post-discharge. 11 Biochemical derangement measured by GNRI was associated with mortality (hospital or 30-day) and hospital LOS, 10,13,14 but not associated with ICU mortality and ICU LOS. 15 Similarly, biochemical derangements measured by CONUT and PNI were not associated with ICU mortality.…”
Section: Prognostic Datamentioning
confidence: 99%